Pelatihan Dasar Pelatih Puslatcab Tulungagung Guna Menghadapi Porprov 2022 - Agus Hariyanto; Gigih Siantoro; Ika Jayadi; Muhammad Kharis Fajar (Inspirasi Nusantara, 2022)
Sport has become a social phenomenon that is spread throughout the world. Sports can be used and directed for various purposes, every country in the world including Indonesia faces challenges to improve achievement in every sport and to maintain the physical fitness of its citizens. Various observations in the field regarding training have not shown good and correct fitness and have not understood the importance of training models for themselves and community groups. This is very likely due to insufficient or inadequate knowledge and meeting standards that can maximize physical fitness, this requires the world to be in a critical condition due to the Covid-19 pandemic. This community service activity in providing basic training for Puslatcab Tulungagung trainers is intended as a preparation for trainers to face the 2022 Porprov to maintain physical fitness by doing physical exercise for athletes and coaching staff during the Covid-19 pandemic era. This activity contains training given to coaches so that they can maintain the physical fitness of athletes and coaching staff of the Tulungagung Regency Puslatcab by doing physical exercises at home which will affect and maintain the body's immune system to avoid contracting the Covid-19 virus.